Stimulation of Cerebral Angiogenesis and Neurogenesis by Transcatheter Intracerebral Laser Photobiomodulation Therapy in Alzheimers Disease (Global Journal of Medical Research, 2022)
Abstract not found
Keywords: alzheimer's disease; photobiomodulation therapy; laser; transcatheter intracerebral laser photobiomodulation therapy; angiogenesis; neurogenesis